Relationship between core competence and professional identity among critical care nurses (急危重症护士核心能力与职业认同感相关性研究) - JIN Jinlong (靳金龙) (中西医结合护理)
Objective To investigate the current condition and relationship of core competence and professional identity among critical care nurses in Guangyuan city, Sichuan Province, and provide reference for advanced skill training and management of critical care nurses. Methods The Competency Inventory For Registered Nurse and Professional Identification Scale were used to investigate 175 critical care nurses in Guangyuan city, Sichuan Province. Results The total score of Competency Inventory For Registered Nurse was (151. 79±38. 25). The total score of Professional Identification Scale was (113. 29±21. 33). There was a positive correlation between core competence and professional identity among critical care nurses(r=0. 517, P＜0. 01). Conclusion Findings of the investigation indicated a moderate level of core competence and professional identity in critical care nurses. Hospital management should take countermeasures to enhance the core competence of nurses, therefore improving their professional identity and further development of nursing service in hospitals. (目的 调查四川省广元地区急危重症护士核心能力及职业认同感现状, 探讨两者的相关性, 为培训和提升急危重症重症护士的专科技能提供依据, 也为医院管理者进行护理管理提供指导。方法 采用中国注册护士核心能力量表和护士职业认同评定量表, 对四川省广元市地区医院的175名急危重症重症护士进行匿名电子问卷调查。结果 急危重症护士核心能力总分为(151. 79±38. 25)分, 急危重症护士职业认同总分为(113. 29±21. 33)分, 急危重症护士核心能力与职业认同呈正相关(r=0. 517, P＜0. 01)。结论 急危重症护士的核心能力及职业认同均处于中等水平, 管理者应关注急危重症护士的核心能力与职业认同, 可以通过提升急危重症护士核心能力, 让急危重症护士的职业认同感获得同步提升, 稳固急危重症护理队伍。)